2009
DOI: 10.1126/science.1174381
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-92a Controls Angiogenesis and Functional Recovery of Ischemic Tissues in Mice

Abstract: MicroRNAs (miRs) are small noncoding RNAs that regulate gene expression by binding to target messenger RNAs (mRNAs), leading to translational repression or degradation. Here, we show that the miR-17approximately92 cluster is highly expressed in human endothelial cells and that miR-92a, a component of this cluster, controls the growth of new blood vessels (angiogenesis). Forced overexpression of miR-92a in endothelial cells blocked angiogenesis in vitro and in vivo. In mouse models of limb ischemia and myocardi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

23
954
3
21

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 1,127 publications
(1,011 citation statements)
references
References 28 publications
23
954
3
21
Order By: Relevance
“…However, the research of Bonauer et al showed that miR-92a inhibited angiogenesis via integrin-α5 in an ischemic model. 9 We speculated that miR92a regulates angiogenesis via different pathways under different conditions. So we determined the integrin-α5 expression level in both the control group and HUA group.…”
Section: Hua Inhibits Angiogenesis In Vitromentioning
confidence: 99%
“…However, the research of Bonauer et al showed that miR-92a inhibited angiogenesis via integrin-α5 in an ischemic model. 9 We speculated that miR92a regulates angiogenesis via different pathways under different conditions. So we determined the integrin-α5 expression level in both the control group and HUA group.…”
Section: Hua Inhibits Angiogenesis In Vitromentioning
confidence: 99%
“…MicroRNAs (miRNAs) act as negative regulators of gene expression [23][24][25][26][27][28][29] . Strikingly, a single miRNA is even able to modulate complex physiological or disease phenotypes by regulating the entire functional networks 26,30,31 .…”
mentioning
confidence: 99%
“…The upstream transcriptional start site of the cluster is highly conserved across vertebrates, contains an extensive CpG island, a core putative promoter regulated by epigenetic modifications 50, 69. Notably, forced‐expression of miR‐92a alone, in ECs was found to block angiogenesis in ischaemia mouse model which has been corresponded to targeting pro‐angiogenic integrin subunit alpha5 24.…”
Section: Some Mirna Key Mechanisms In Reparative Angiogenesismentioning
confidence: 99%